Perspectivas de la Investigación Contable en Estudiantes Colombianos, una Evaluación Preliminar a la Producción Académica (2018)
This paper analyzes the academic production of undergraduate students of the public accounting program in different magazines of the country (adversary, agora, criteria, accounting identity and assets) during the period 2011-2015, identifying posible advancesor limitations in the accounting research to the light of epistemological, ontological and methodological approaches. The methodology used is quantitative and qualitative, using content analysis to classify the articles according to the research approaches. From authors read in the state of the art, the hypothesis is that most articles will be classified in an orthodox, technical, empirical or positive approach.